Religio-spiritual strategies of self-help and empowerment in everyday life: selected cases of spirituality in Germany - Königstedt, Christiane (Scripta Instituti Donneriani Aboensis, 2012)
Within the wider context of contemporary spiritual practice or esotericism, individuals can be observed (not only in Germany but also elsewhere), who combine different kinds of alternative healing practices in order to gain or maintain physical and mental health, well-being, success and autonomy. These practices were said to take place only within the very private sphere, partly because those beliefs do not change the everyday lifestyles of individuals significantly, at least in comparison with the much more formative traditional religions. These practices are often connected to discernibly spiritual or religious, often inconsistent combinations of beliefs that contain a ‘multiple salvation logic’ which is used by the actors themselves to explain why they act in certain ways. At the same time, key features of ‘secular rationality’ are a central aspect as well; for example, the level of semantics, which here is ‘the secular’, is a category actively and deliberately, though implicitly applied, positively defined (for example, as scientific) and constantly placed in relation to the categories of ‘spiritual’ and ‘religious’. These also are transformed, but always remain structurally recognisable within the differently reported world-views, especially if one considers instrumental rationality as something widely associated with the ‘secular’ in contrast with the ‘religious’ or ‘spiritual’. This paper shows, firstly, the different versions of salvation logic and reasoning of action within individual world-views, and secondly it focuses on examples of the semantics used in reports of individuals’ own world-views. Thirdly, against this backdrop, the term ‘post-secular’, understood in this way, as opposed to its original meaning, is discussed in order to point out former limits and some new possibilities when this term is used as a description of current forms of religion.